2010
DOI: 10.3855/jidc.632
|View full text |Cite
|
Sign up to set email alerts
|

Ovine clone ST1464: A predominant genotype of Staphylococcus aureus subsp. anaerobius isolated from sheep in Sudan

Abstract: Background: The aim of the present study was to examine the phenotypic and genotypic relatedness of 17 Staphylococcus aureus subsp. anaerobius isolates recovered from sheep abscesses in Khartoum state, Sudan, during the period [2007][2008]. Methodology: This sample was characterised using antibiogram typing, biochemical typing with the commercial PhenePlate system (PhP-CS) and multilocus sequence typing (MLST). Results: Low levels of resistance were noted to the 11 antimicrobial agents tested. All the isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…MLST was performed with selected strains from all countries as well as from all PFGE subtypes. They all corresponded to the same ST1464, which was first described in 2010 by Elbir and others (2010) as causing abscesses in sheep in Sudan. All Swiss isolates were shown to belong to ST1464.…”
Section: Discussionmentioning
confidence: 81%
“…MLST was performed with selected strains from all countries as well as from all PFGE subtypes. They all corresponded to the same ST1464, which was first described in 2010 by Elbir and others (2010) as causing abscesses in sheep in Sudan. All Swiss isolates were shown to belong to ST1464.…”
Section: Discussionmentioning
confidence: 81%
“…Representative isolates of all PFGE subtypes as well of all countries belonged to the same sequence type (ST), ST1464, which was a singleton, and to the agr type II. Further, Elbir et al [66] has also reported that 17 Saan isolates were shown to have the same phenotypic and genotypic characteristics. It is well known that S. aureus produces many virulence factors, such as hemolysins, leukocidins, proteases, enterotoxins, exfoliative toxins, and immune-modulatory factors [67].…”
Section: Saanmentioning
confidence: 94%
“…anaerobius strain ST1464 sequenced in this study was isolated from an abscess in the prescapular region of a sheep with Morel's disease in Khartoum state, Sudan [6]. S. aureus subsp.…”
Section: Classification and Featuresmentioning
confidence: 96%
“…anaerobius) is a Gram positive bacterium of veterinary interest and is responsible for Morel's disease, which is characterized by chronic subcutaneous abscesses near superficial lymph nodes in sheep and goat [1]. Morel's disease was described in Sudan, Saudi Arabia, Hungary, Spain, Denmark, Italy and Poland [1][2][3][4][5][6][7]. The only report of human infection was a case of septicemia in an Australian patient [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation